2016
DOI: 10.1542/peds.2015-2360
|View full text |Cite
|
Sign up to set email alerts
|

Influenza in Infants Born to Women Vaccinated During Pregnancy

Abstract: BACKGROUND: Infants <6 months old with influenza are at risk for adverse outcomes. Our objective was to compare influenza outcomes in infants <6 months old born to women who did and did not report influenza vaccine during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 24 publications
3
62
1
3
Order By: Relevance
“…14 Studies have shown that maternal influenza vaccination can prevent influenza in infants; therefore, pregnant women should receive influenza vaccination to protect their infants. 15,16 The age-group 6 month to <5 years was the largest cohort (54%) with the second-highest hospitalization rate and the highest complication rate (30.6%) especially neurologic, similar to another study. 17 In other studies, the age-group 6-35 months or the lowest agegroups had the highest incidence of complications.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…14 Studies have shown that maternal influenza vaccination can prevent influenza in infants; therefore, pregnant women should receive influenza vaccination to protect their infants. 15,16 The age-group 6 month to <5 years was the largest cohort (54%) with the second-highest hospitalization rate and the highest complication rate (30.6%) especially neurologic, similar to another study. 17 In other studies, the age-group 6-35 months or the lowest agegroups had the highest incidence of complications.…”
Section: Discussionsupporting
confidence: 83%
“…11,16 20,24 In two published studies, encephalitis, encephalopathy, and febrile seizures constituted 0.6%-4.4% of influenza admissions, whereas these constituted 10.3% of our admissions. 16,20 In a study of influenza vaccine uptake, only 51% and 46% of physicians recognized epilepsy and intellectual disability as high-risk conditions. 25 Physicians should routinely offer influenza vaccination to patients with a prior seizure disorder, neurologic conditions or developmental delay.…”
Section: Discussionmentioning
confidence: 87%
“…Instead, the preferred strategy for preventing influenza in this age group is through the vaccination of pregnant women. Although clinical trials and observational studies have both reported a protective effect of maternal influenza vaccination on infections in babies aged <6 months [5][6][7], this appears to be limited to the first 8 weeks of life [8].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, that study was the only RCT designed a priori with a (co-)primary outcome of low birthweight, and therefore the only trial powered to detect a difference in birthweight between the 2 groups. In addition to data from clinical trials, results from multiple recent observational studies have also demonstrated a consistent beneficial impact of maternal influenza immunization on a variety of fetal and infant outcomes (2124). …”
mentioning
confidence: 97%